Diagnostic features of community‐acquired pneumonia in children: what's new?. (December 2013) - Chiappini, Elena; Venturini, Elisabetta; Galli, Luisa; Novelli, Vas; de Martino, Maurizio
Abstract: Aim: To critically summarise the available data on diagnosis of CAP in children, focusing on the newest findings and on the need for new studies. Methods: Eighty studies on the diagnosis of paediatric community‐acquired pneumonia were scrutinised. Results: We found no significant associations between the signs or symptoms and aetiology of pneumonia and concluded that chest radiographs remain controversial and real‐time polymerase chain reaction appears more sensitive than blood cultures. Conclusion: Antibiotic overuse could make it difficult to differentiate viral and bacterial causes. Molecular methods provide promising tools for diagnosing infection by atypical bacteria, but are expensive and should be used selectively.